2013
DOI: 10.2174/1389202911314020007
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Transforming-Growth-Factor-β1 Gene in Late-Onset Alzheimer’s Disease: Implications for the Treatment

Abstract: Late-onset Alzheimer's disease (LOAD) is the most common form of dementia in the elderly. LOAD has a complex and largely unknown etiology with strong genetic determinants. Genetics of LOAD is known to involve several genetic risk factors among which the Apolipoprotein E (APOE) gene seems to be the major recognized genetic determinant. Recent efforts have been made to identify other genetic factors involved in the pathophysiology of LOAD such as genes associated with a deficit of neurotrophic factors in the AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 118 publications
0
27
0
Order By: Relevance
“…An increase in cytokine expression led to a decreased tendency of a rapid reaction to stimuli (morbid, stressful, emotional). Numerous studies allow one to claim that signal pathways of TGFβ1 and BDNF, mediated by SMAD proteins in the induction of disturbances of sensitivity, emotional resistance and mood (mainly depression) in the course of chronic inflammatory diseases play here a great role [60,64,65,66,67]. Thus, in the study the authors emphasized the role and importance of selected molecular markers (SNP Tth111I of NR3C1 gen and TGFβ1 expression).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in cytokine expression led to a decreased tendency of a rapid reaction to stimuli (morbid, stressful, emotional). Numerous studies allow one to claim that signal pathways of TGFβ1 and BDNF, mediated by SMAD proteins in the induction of disturbances of sensitivity, emotional resistance and mood (mainly depression) in the course of chronic inflammatory diseases play here a great role [60,64,65,66,67]. Thus, in the study the authors emphasized the role and importance of selected molecular markers (SNP Tth111I of NR3C1 gen and TGFβ1 expression).…”
Section: Discussionmentioning
confidence: 99%
“…LOAD form accounts for more than 90% of AD cases [30]. To date, the APOE gene is the major genetic factor in LOAD susceptibility [31], while other genetic factors related with LOAD susceptibility remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Signal sequence regulates posttranslational protein synthesis which finally affects the level of expression, secretion of this cytokine results in low or high TGFβ1 plasma levels [14]. It has been demonstrated that the transition at codon 25 of GNC (ArgNPro substitution) reduces the secretion and plasma levels of TGFβ1 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…and the Leu (T) allele [32,33], whereas others related it to the Pro (C) allele [15]. Changes at both codon 10 and 25 result in an alteration to the hydrophobic α-helix of the signal peptide sequence, thereby reducing its ability to direct protein transport across the endoplasmic reticulum [14,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation